Solvent Role in Molecular Recognition of Patchouli Extraction Process - Fatmawati, Adam; Siti Hana, A. B.; Saiful Nizam, Tajuddin; M. M., Yusoff (Asian Publication Corporation, 2016)
Patchouli or Pogostemon cablin Benth is an aromatic plant of importance to the fragrant and cosmetic industries. Its secondary metabolites present interesting pharmacological benefits such as antioxidant and antimutagenic properties. This work is an extended study of the published work in ethanol and water solvents using Ewald summation method and mass spectra characterization of patchouli essential oil extracted with three different polar and non-polar solvents. Ewald summation method has reproduced a better radical distribution function (rdf) intensity in the polar ethanol and water solvents using COMPASS force-field. This work concludes that the complex molecular interaction particularly hydrogen bonding play a significant role to affect the solubility of patchoulol solute either in polar or non-polar solvents during the extraction process.